IMPLEMENTASI WEBSITE PROFILE PENGINAPAN “BAGOES VIEW COTTAGES” MANINJAU - Hafizah Hanim; Ricky Akbar; Husnil Kamil; Fajril Akbar; Rahmatika Pratama S; Afriyanti Dwi Kartika; Dwi Welly Sukma N; Adi Arga Arifnur; Surya Afnarius; Hasdi Putra; Haris Suryamen; Jefril Rahmadoni; Aina Hubby Aziira; Ullya Mega Wahyuni; Febby Apri Wenando; Lova Endriani Zen (Bajang Institute, 2025)
A website is a crucial digital marketing tool that helps businesses provide comprehensive information and increase customer confidence. Previously, Bagoes View Cottages, a guesthouse near Maninjau Lake, relied solely on Instagram for online marketing, which led to a lack of credibility among prospective visitors. Building a professional profile website is the goal of this community service project in order to improve the cottage's online visibility and promote better marketing results. Three phases comprised the activities: planning, execution, and reporting. Coordinating with the cottage management to collect the necessary images and text was part of the preparatory phase. The team created the website and carried out a formal handover to the owner throughout the deployment phase. The finished website, which can be found at http://bagoesviewcottages.com, offers a wealth of information, including room specifications, rates, and contact data. The website has been well received and is anticipated to raise awareness and draw more guests to Bagoes View Cottages.